The Heat-Stable Enterotoxin Receptor, Guanylyl Cyclase C, as a Pharmacological Target in Colorectal Cancer Immunotherapy: A Bench-to-Bedside Current Report - Baybutt, Trevor R. (Toxins (Basel), 2017)
Cancer immunotherapy is becoming a routine treatment modality in the oncology clinic, in spite of the fact that it is a relatively nascent field. The challenge in developing effective immunotherapeutics is the identification of target molecules that promote anti-tumor efficacy across the patient population while sparing healthy tissue from damaging autoimmunity. The intestinally restricted receptor guanylyl cyclase C (GUCY2C) is a target that has been investigated for the treatment of colorectal cancer and numerous animal, and clinical studies have demonstrated both efficacy and safety. Here, we describe the current state of GUCY2C-directed cancer immunotherapy and the future directions of this work.